Prediction of oxygen uptake from power output on a Concept II ergometer in Danish elite rowers - Larsson, B.; Jensen, K. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
To evaluate the relationship between oxygen uptake and work load in ergometer rowing eight female, open class (FH) and ten male lightweight (ML) elite rowers performed an incremental test to volitional exhaustion on a Concept II ergometer. The work rate started at 130/200 watt, and increased incrementally by 30/40 watt (FH/ML) every 5-min. Stroke rate started at 20 strokes/min, and increased by 2 strokes/min every 5-min. The subjects (FH/ ML) had a mean± SD age, height, weight, fat free weight, and VO2max of 24.5± 3.2/ 24.9± 2.8 yrs, 182.3± 4.8/ 186.4± 5.2 cm, 79.2± 4.6/ 78.3± 2.2 kg, 59.1± 3.5/ 68.6± 2.5 kg, 4.2± 0.2/ 5.2± 0.5 l/min.